Trauma and suicidality in war affected communities - Janković, Jelena (Array, 2013)
Purpose The aim was to assess whether experiences of war trauma remain directly associated with suicidality in war affected communities when other risk factors are considered. Materials and methods In the main sample 3313 participants from former Yugoslavia who experienced war trauma were recruited using a random sampling in five Balkan countries. In the second sample 854 refugees from former Yugoslavia recruited through registers and networking in three Western European countries. Sociodemographic and data on trauma exposure, psychiatric diagnoses and level of suicidality were assessed. Results In the main sample 113 participants (3.4%) had high suicidality, which was associated with number of potentially traumatic war experiences (odds ratio 1.1) and war related imprisonment (odds ratio 3) once all measured risk factors were considered. These associations were confirmed in the refugee sample with a higher suicidality rate (10.2%). Discussion and conclusions Number of potentially traumatic war experiences, in particular imprisonment, may be considered as a relevant risk factor for suicidality in people affected by war.